Sexual Harassment at Workplace Awareness Among Employer And Employees In Pekan, Pahang - Faiz, Azizul; Diyana, Kamarudin; Haziman, Zakaria; Alya Zakirah, Abdul Mutalif; Ame, Abdullah (HDF International, 2023)
Most sexual harassment cases in the workplace go unreported because the victims are unaware of what constitutes sexual harassment. They may have remained silent due to embarrassment and fear of losing their jobs and consequently had to suffer in silence. This qualitative study seeks to investigate the current issues of sexual harassment in the workplace in Pekan, Pahang, as well as the level of awareness among employers and employees regarding the matter. In addition to identifying the current policy used in the workplace, one of the specific objectives of this research is to identify the types of conduct that constitute sexual harassment and to propose solutions for sexual harassment in the workplace. Interviews, existing documents, and a questionnaire were analyzed using a triangulation technique for the data collection. Thirty respondents from public and private companies in Pekan, Pahang, provided data. Six participants were invited to share their experiences with sexual harassment in the workplace. To ensure the reliability and validity of this qualitative research, the four criteria, which are credibility, transferability, conformability, and authenticity, are evaluated. The researcher transcribed the interview data before qualitative thematic coding analysis. The themes presented in the research are sexual perpetrators in the workplace, awareness, female victims from non-management, and the victim's emotions and actions in response to sexual harassment. In the meantime, the subthemes are the victim's experience with sexual harassment and employer and employee awareness regarding sexual harassment in the workplace.